Comparison of brain magnetic resonance imaging findings before and after liver transplantation - Kural Rahatli, Feride; Kahraman, Gokhan; Yildirim Donmez, Fuldem; Akdur, Aydincan; Muhtesem Agildere, Ahmet; Haberal, Mehmet (Annals of Medical Research, 2021)
None
Keywords: s: Liver Transplantation; Brain MRI; Manganese Deposition; Copper Deposition.